Sebaceous Adenoma in a Geriatric Poodle Dog: A Case Report - Winaya, Ida Bagus Oka; Adi, Anak Agung Ayu Mirah; Sudimartini, Luh Made; Merdana, I Made; Sudipa, Putu Henrywaesa; Pemayun, I Gusti Agung Gde Putra; Sewoyo, Palagan Senopati (Universitas Airlangga, 2024)
A 14-year-old black male Poodle was brought to the Animal Teaching Hospital, Udayana University by its owner with clinical signs of frequent licking of its left front paw. Upon examination, red bumps were observed on the left front leg, accompanied by small, round black spots scattered on the dorsal side of the body. Additionally, black nodules were present on the lower eyelids and hind limbs. Surgical intervention was undertaken to excise the tumor mass, with the animal under anesthesia induced by ketamine at 5 mg/kg BW intravenously. The reddish nodule was excised by performing an elliptical incision at the base of tumor. Postoperatively, the animal received an antibacterial injection comprising ceftriaxone and tazobactam at 25 mg/kg BW intramuscularly and antiseptic wound dressing for supportive care. Microscopic examination revealed neoplastic cells arranged into lobules of varying sizes and shapes within the tumor mass. These lobules consisted of differentiated sebocytes and basaloid cells. At the periphery of the neoplastic lobules, the basaloid cells displayed several layers and exhibited invasion with moderate anisocytosis. The mitotic index was no more than ten cells in one field of view. Based on these histopathological features, the tumor was confirmed to be a sebaceous adenoma. After a 10-month follow-up period, there were no signs of tumor recurrence observed.